Bacterial Indicators/Health Hazards Associated With Water 1977
DOI: 10.1520/stp34819s
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens as a Water Quality Indicator

Abstract: Clostridium perfringens and the more general group to which it belongs, “sulfite-reducing, spore forming anaerobes,” are considered with regard to their use as health effects, water quality indicators. The groups are examined with regard to their identification, their importance, the characteristics which impinge on their use as indicators, monitoring applications, available evaluation data, and enumeration methods. C. perfringens has specific and limited applications as a water quality indicator. It appears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Since SecA causes vesicle aggregation, two lipid-binding domains must be present to cause inter-bilayer contact. Assuming that SecA is active as a dimer [16,17] at least two possible explanations for this effect can be provided. Either the two monomers of SecA in the dimer each possess one lipid-binding site which have different orientations with respect to the membrane such that two vesicles can be bound simultaneously by the dimer, or the two monomers in the dimer have the same orientation towards the membrane but possess two lipid-binding sites per monomer.…”
Section: Characterisation Of the Seca-mediated Vesicle Aggregutionmentioning
confidence: 99%
“…Since SecA causes vesicle aggregation, two lipid-binding domains must be present to cause inter-bilayer contact. Assuming that SecA is active as a dimer [16,17] at least two possible explanations for this effect can be provided. Either the two monomers of SecA in the dimer each possess one lipid-binding site which have different orientations with respect to the membrane such that two vesicles can be bound simultaneously by the dimer, or the two monomers in the dimer have the same orientation towards the membrane but possess two lipid-binding sites per monomer.…”
Section: Characterisation Of the Seca-mediated Vesicle Aggregutionmentioning
confidence: 99%
“…Edberg et al (2000 and Odonkor and Ampofo (2013 reported that EC was the best indicator of the bacteriological quality of water in most examined habitats. CP seems to be the choice in published literature for measuring past or intermittent pollution and in circumstances where resistance to disinfectants and environmental stress was highest (Cabelli ,1977).…”
Section: Performance Of Fibmentioning
confidence: 99%